African muslim diaspora: the genesis of contemporary global islamic radicalism (2015)
African diaspora is a phenomenal history of primordial occurrence ostensibly buried alive in a shallow grave. Its seeming resurrection in contemporary time has become a reality seeking a global attention. One of the flying wings of that reality which can never be clipped is religion. Being a diehard cultural pivot, religion connotes different things to different people at different times. It is the totality of life to the average living majority of African Muslims in diaspora. Religion, especially Islam, in contemporary time, has become a form of science that requires a concentrate study by all and sundry. This is because religion has graduated from its hitherto personal status into an interpersonal one with global security implications. Most people now see the unfortunate incident of terrorism that occurred in United States on September 11, 2001 as the genesis of the current global Islamic radicalism. This view totally contradicts historical facts as it undermines the real cause of today’s religious restiveness around the world. More than a decade before the US terrorism incident, there had been a signal pointing towards a possible religious turbulence at the dawn of the 21st century. But the signal was tactically ignored and treated as a non-issue. Today, many factors, like slave trade, religious dichotomy and economic insensitivity of former colonial masters still remind Africans in diaspora of their conditions. That reminder is like a whirl wind which should be calmed to allow peace in the 21st century. The modalities to adopt for it are some of the issues to be addressed in the body of this paper.